PENGARUH KEMITRAAN BERKELANJUTAN DALAM BISNIS STRATEJIK UMKM KONVEKSI SERAGAM FASHA DI KOTA INDUSTRI CIKARANG - Ida Agustina, (Journal of Innovation Research and Knowledge, 2025)
The strategic business development of Fasha SME uniform convection in the Cikarang industrial area depends significantly on sustainable partnerships between SMEs, corporations, and the supply chain network. This research aims to analyze how collaborative relationships enhance business efficiency, market competitiveness, and long-term sustainability. Using a qualitative and quantitative approach, data was collected through interviews, observations, and financial performance analysis of SMEs engaging in sustainable practices. The findings indicate that SMEs with strong partnerships in supply chains benefit from greater access to high-quality materials, advanced technology, and cost efficiency, leading to increased production capacity and market reach. Additionally, strategic alliances improve financial resilience and business adaptability amidst economic fluctuations. The implications of this study suggest that structured business networks, government incentives, and sustainability policies play a crucial role in fostering SME growth in the industrial sector. Strengthening cooperation between SMEs and large enterprises will accelerate the transition to eco-conscious manufacturing, ensuring the long-term success of small businesses in Cikarang’s industrial ecosystem